Seismic Ground Response Analysis of Input Earthquake Motion and Site Amplification Factor at KUET - Sonia Akter (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2021)
Ground motion is the movement of the earth's surface due to explosions or the propagation of seismic waves. In the seismic design process, ground response analysis evaluates the impact of local soil conditions during earthquake shaking. However, it is difficult to determine the dynamic site response of soil deposits in earthquake hazard-prone areas. Structural damage has a great influence on the selection of input ground motion, and in this study, the importance of bedrock motion upon the response of soil is highlighted. The specific site response analysis is assessed through “DEEPSOIl